Spiritual or religious struggle in hematopoietic cell transplant survivors. Issue 2 (15th November 2015) - King, Stephen Duane; Fitchett, George; Murphy, Patricia E.; Pargament, Kenneth I.; Martin, Paul J.; Johnson, Rebecca H.; Harrison, David A.; Loggers, Elizabeth Trice
Abstract: Background: This study describes the prevalence of religious or spiritual (R/S) struggle in long‐term survivors after hematopoietic cell transplantation (HCT), demographic and medical correlates of R/S struggle, and its associations with depression and quality of life. Methods: Data were collected in conjunction with an annual survey of adult (age ≥18 years) survivors of HCT. Study measures included R/S struggle (negative religious coping, NRC, from Brief RCOPE), measures of quality of life (subscales from 36‐item Short Form Health Survey and McGill), and the Patient Health Questionnaire 8. R/S struggle was defined as any non‐zero response on the NRC. Factors associated with R/S struggle were identified using multi‐variable logistic regression models. Results: The study analyzed data from 1449 respondents who ranged from 6 months to 40 years after HCT. Twenty‐seven percent had some R/S struggle. In a multi‐variable logistic regression model, R/S struggle was associated with greater depression and poorer quality of life. R/S struggle was also associated with younger age, non‐White race, and self‐identification as either religious but not spiritual or spiritual but not religious. R/S struggle was not associated with any medical variables, including time since transplant. Conclusions: Religious or spiritual struggle is common among HCT survivors, even many years after HCT. Survivors should be screened and, as indicated, referred to a professional with expertise in R/S struggle. Further study is needed to determine causal relationships, longitudinal trajectory, impact of struggle intensity, and effects of R/S struggle on health, mood, and social roles for HCT survivors. Copyright © 2015 John Wiley & Sons, Ltd.